AO spine clinical practice recommendations for the surgical management of degenerative spondylolisthesis: when to de compress alone and when to fuse - Martin, Christopher T.; Ambrosio, Luca; Cabrera Cousino, Juan P.; Chen, Xiaolong; Cheung, Jason P. Y.; Hamouda, Waeel; Le, Hai V.; Louie, Philip K.; Muthu, Sathish; Singh, Hardeep; Soliman, Mohamed A. R.; Sotirios, Veranis; et al. (Global spine journal, 2025)
Study Design Literature review. Objective To provide a concise review of outcomes of decompression and fusion (D + F) vs decompression (D) alone for degenerative lumbar spondylolisthesis (DLS). Methods 6 articles were selected, including 3 randomized clinical trials (RCT), 2 meta-analyses, and 1 radiographic cohort study. Summarized factors affecting the outcomes of D + F vs D alone for DLS and provide expert level clinical recommendations. Results Ghogawala included DLS patients showing improved SF-36 scores (P = 0.046) and lower re-operation rates (P = 0.05) in D + F patients compared to D alone. Forsth, included patients with stenosis both with and without DLS, and showed no difference in any reported outcome measure or reoperation rate. Austevoll included DLS patients that found that D alone was non-inferior to D + F in the primary outcome measure of ODI reduction at 2-year after surgery. Gadjradi included studies showing higher morbidity in the D + F group, as compared to D alone. Shukla included studies which found there was no difference in the raw patient outcome scores at final follow-up. Blumenthal included DLS patients who received D and reported disc height of >6.5 mm, facet angle >50 degrees, and dynamic motion >1.25 mm were associated with high re-operation rates (45%, 39%, and 54% respectively). Conclusions The RCT's and meta-analyses report contradictory conclusions and no blanket statement regarding the efficacy of D + F vs D alone can be made for all patients with DLS. Surgeons should closely review pre-operative imaging for signs of instability in order to better identify appropriate patients for each indication.
Online veröffentlicht: June 11, 2025
Gesehen am 04.11.2025